GREEN LOAN BANKS POLICY TO PROVIDE ENVIRONMENT FRIENDLY PROJECT - Tri Handayani; Lastuti Abubakar; C. Sukmadilaga (Fakultas Hukum, Universitas Diponegoro, 2020)
Banks have an important role in realizing SDGs, therefore the Bank must continue to develop its products and services to be directed towards sustainable economic activities and not too exploring resources. Based on The Appendix of the President Decree No. 59/2017 the Indonesian government directed the global target of economies inclusive regarding the participation of the financial services sector. The Banks will support the priority economic sectors development such as agriculture, processing industries, and infrastructure, Micro, Small, Medium Enterprises and Energy. Banks can participate by using a green loan policy. This research is a normative legal research, which focuses on examining the application of the rules or norms in positive law. The result is the Banks play a key role in society, banks have purpose to help develop sustainable economies and to empower people to build better futures. When banks will give a credit to those who have a business that has a direct impact to the environment, bank also can be offer a position as a manager of environmental recovery guarantee funds. In other side, Banks can provide green development, in a process of giving credit to the debtor; banks need to pay attention to the business legality of prospective debtors. Banks are required to ensure that prospective customers have a legal business and comply with all relevant laws and regulations.